'Working as a Real Nurse': Nursing Students' Experiences of a Clinical Education Ward in Psychiatric Care. (2nd November 2021) - Vuckovic, Verica; Carlson, Elisabeth; Sunnqvist, Charlotta
Abstract: Although the concept of clinical education wards has shown encouraging outcomes regarding nursing students' satisfaction with clinical placements in somatic care, the existing research in a psychiatric context is sparse. This study aims to explore nursing students' experience during clinical education at a psychiatric clinical education ward. A qualitive descriptive study with content analysis, using interviews with 16 bachelor's degree nursing students was conducted. The results indicated that an enriched and adapted learning environment focusing on psychiatric nursing with peer learning supported independence and progression into the future nursing role.